USING ECONOMIC MECHANISMS TO INCREASE THE COMPETITIVENESS OF TEXTILE INDUSTRY ENTERPRISES (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
The competitiveness of textile industry enterprises depends not only on production volume, labor cost, or access to raw materials, but also on the quality of economic mechanisms that regulate costs, investment, innovation, market positioning, and value-chain integration. In modern textile markets, enterprises operate under the pressure of global competition, technological modernization, sustainability standards, and changing consumer demand. Therefore, competitiveness must be understood as a systemic economic category that combines productivity, financial stability, product differentiation, export capacity, technological renewal, and responsible supply-chain governance.